The art of client service : the classic guide, updated for today's marketers and advertisers - Solomon, Robert (Hoboken, New Jersey : John Wiley & Sons, Incorporated, 2016)
"In a letter to the author, advertising agency Ogilvy & Mather's Chair and CEO emeritus Shelly Lazarus said, "The book is terrific. It's an easy read, and I agree with every word." Danny Meyer, legendary restaurateur and CEO of the Union Square Hospitality Group, described the book as providing, "sensible, timeless advice for distinguishing your brand through generosity of spirit." This book outlines how to build better client relationships and work smarter with colleagues. It transforms what is viewed as an elusive, even ephemeral pursuit, not easily characterized by a precise skill set or inventory of responsibilities, into something definable and actionable, governed by a precise checklist of things designed to help guide work. The new version begins with a synthesis discussions the author has had with a wide range of advertising and marketing people about "what's wrong with advertising," setting up the material to follow. It ends with a provocative question, "Is account management dead," that the author counters in convincing fashion. In between there is practical, accessible content designed to help people get better at what they do"--
Machine generated contents note: Dedication Foreword Introduction 1. What Makes Great Client Service? PART ONE: HOW TO BE GREAT WITH CLIENTS 2. Account Management's Role 3. Achieving The Next Level 4. Transforming A Career Into A Calling PART TWO: WINNING NEW BUSINESS FOR YOUR AGENCY 5. New Business: What It Is, Why It Is Important, And Why You Should Give A Damn 6. How To Contribute Before, During, And After Pitch Day 7. Getting To Yes PART THREE: BEGINNINNG A CLIENT RELATIONSHIP 8. In A High-Tech World, Be Low-Tech 9. What Success Looks Like 10. Always Manage Client Expectations From The Outset 11. Be Multilingual 12. Live The Client's Brand 13. Ask, "What Do My Colleagues Need To Create Great Advertising?" Then Deliver It PART FOUR: HOW TO.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Advertising; Marketing; Customer relations; Electronic books